Determinants of Latent Tuberculosis Infection (LTBI) among Health Workers in Community Health Centers, Makassar City: A Case-Control Study - Nofian, Elia; Masni, Masni; Maria, Ida Leida; Noor, Nur Nasry; Arsyad, Muhammad (International Journal of Statistics in Medical Research, 2026)
The prevalence of latent tuberculosis infection (LTBI) in Asia reaches 36% based on Tuberculin Skin Test (TST) results, and healthcare workers represent a high-risk group for occupational TB exposure. In South Sulawesi Province, 2,488 LTBI cases were reported in 2024, with Makassar City contributing the highest number. This study aimed to identify determinants of LTBI among healthcare workers in community health centers in Makassar City using a retrospective case-control design. Cases were healthcare workers with positive TST results recorded in the SITB database, while controls were healthcare workers from the same centers with negative TST results selected through simple random sampling with a 1:1 ratio. Bivariate analysis was conducted using Odds Ratios (OR), and variables with p < 0.25 were included in a multivariate logistic regression model to determine independent factors. A total of 316 cases and 316 controls were analyzed. Inconsistent mask use (AOR = 5.20; 95% CI: 3.60–7.51), history of contact with TB patients (AOR = 2.63; 95% CI: 1.82–3.80), and absence of BCG immunization (AOR = 2.30; 95% CI: 1.50–3.53) were independently associated with LTBI. Although smoking was significant in bivariate analysis, it was not retained in the final multivariate model. These findings highlight the importance of strengthening infection prevention and control practices and routine LTBI screening among healthcare workers in primary healthcare settings.